Heterogeneous impacts of China's economic and development zone program. (30th September 2019) - Howell, Anthony
Abstract: This paper examines the impact of economic and development zones (EDZs) on the productivity of incumbent firms in China. To deal with the selection issue, I first take into account potentially different selection mechanisms across two popular types of EDZs—economic and technological development zones (ETDZs) and high‐tech development zones (HTDZs)—by relying on multiple treatment propensity scores matching techniques. Next, I apply the difference‐in‐differences estimator to the matched sample and conduct an event study analysis. The results show that the respective effects of ETDZs and HTDZs on firm productivity are positive, but subject to a nonlinear trend over time. The size of the productivity gains depends critically on the type of EDZ, however. A new HTDZ (ETDZ) leads to an average productivity gain of up to 30.2% (18.4%) for incumbent firms in the 5 years after the zone was created. These findings suggest that the size of productivity spillovers for spatially targeted firms differ quite significantly depending on the strategic development and policy goals of the EDZ: HTDZs that focus on promoting indigenous‐based factors of learning lead to higher productivity spillovers compared with ETDZs that focus on promoting extra‐local linkages.